Planetary Boundaries and the Doughnut frameworks: A review of their local operability. (September 2022) - Ferretto, Anna; Matthews, Robin; Brooker, Rob; Smith, Pete
Abstract: The concept of Planetary Boundaries has sparked debate around tipping points and the limits of the Earth System for over a decade. Among the most investigated aspects is how to downscale this global concept to a country level, to make it operative at scales at which decisions are taken and policies applied. Specifically how to achieve applicability locally while keeping global relevance, however, remains unclear. The same is true for the "Doughnut" concept, which builds on the Planetary Boundaries framework and adds a social component to create a "Safe and Just Operating Space" (SJOS) within which humanity should live. This paper reviews these two concepts in detail, focusing on their local operability. Synthesis of the literature reveals that, during the downscaling process, either the global meaning of the Planetary Boundaries or the local characteristics of a country are lost. Further, the SJOS remains a very theoretical concept because a match does not exist between the Planetary Boundaries and the social components of the Doughnut. Identification of this problem therefore suggests that future work should calculate the Planetary Boundaries globally for each ecosystem first, and then downscale them by country. In this way, the global relevance of the Planetary Boundaries would hold, and the framework could apply to local policies. Furthermore, the ecosystem services could link the Planetary Boundaries with the social aspects of the Doughnut, and hence contribute to understanding why a country lies within or outside the SJOS.